Clays and Clay Minerals, Vol. 55, No. 1, 96–107, 2007. - Jaisi, Deb P.; Dong, Hailiang; Kim, Jinwook; He, Ziqi; Morton, John P. (The Clay Minerals Society, 2007)
Clay particle aggregation affects a number of environmental processes, such as contaminant sorption/desorption, particle movement/deposition, and sediment structure and stability, yet factors that control clay aggregation are not well understood. This study was designed to investigate how microbial reduction of Fe(III) in clay structure, a common process in soils and sediments, affects clay-particle aggregation. Microbial Fe(III) reduction experiments were conducted with Shewanella putrefaciens CN32 in bicarbonate buffer with structural Fe (III) in nontronite as the sole electron acceptor, lactate as the sole electron donor, and AQDS as an electron shuttle. Four size fractions of nontronite (D5-D95 of 0.12-0.22 mm, 0.41-0.69 mm, 0.73-0.96 mm and 1.42-1.78 mm) were used to evaluate size-dependent aggregation kinetics. The extent of Fe(III) bioreduction and the amount of exopolysaccharide (EPS), a major biopolymer secreted by CN32 cells during Fe(III) bioreduction, were measured with chemical methods. Nontronite particle aggregation was determined by photon correlation spectroscopy and scanning electron microscopy. The maximum extent of Fe(III) bioreduction reached 36% and 24% for the smallest and the largest size fractions, respectively. Within the same time duration, the effective diameter, measured at 95% percentile (D95), increased by a factor of 43.7 and 7.7 for these two fractions, respectively. Because there was production of EPS by CN32 cells during Fe(III) reduction, it was difficult to assess the relative role of Fe(III) bioreduction and EPS bridging in particle aggregation. Thus, additional experiments were performed. Reduction of Fe(III) by dithionite was designed to examine the effect of Fe(III) reduction, and pure EPS isolated from CN32 cells was used to examine the effect of EPS. The data showed that both Fe(III) reduction and EPS were important in promoting clay mineral aggregation. In natural environments, the relative importance of these two factors may be dependent on local conditions. These results have important implications for understanding factors in controlling clay particle aggregation in natural environments.
Nontronite Particle Aggregation Induced By Microbial Fe(iii) Reduction And Exopolysaccharide Production
Clays and Clay Minerals, Vol. 55, No. 1, 96–107, 2007. Nontronite Particle Aggregation Induced By Microbial Fe(iii) Reduction And Exopolysaccharide Production. Deb P. Jaisi; Hailiang Dong; Jinwook Kim; Ziqi He; John P. Morton. DOI: 10.1346/CCMN.2007.0550108. Copyright © 2007, The Clay Minerals Society.
Keywords: Periodicals; Geology; Aggregation; Electrophoretic Mobility; EPS; Fe(III) Reduction; Nontronite; SEM; Shewanella Putrefaciens